Differences in the association of total versus local coronary artery calcium with acute coronary syndrome and culprit lesions in patients with acute chest pain: The coronary calcium paradox. (July 2018) - Puchner, Stefan B.; Mayrhofer, Thomas; Park, Jakob; Lu, Michael T.; Liu, Ting; Maurovich-Horvat, Pal; Ghemigian, Khristine; Bittner, Daniel O.; Fleg, Jerome L.; Udelson, James E.; Truong, Quynh A.; Hoffmann, Udo; et al.
Abstract: Background and aims: Total coronary artery calcium (CAC) burden is associated with an increased cardiovascular risk, while local CAC may represent stable plaques. We determined differences in relationship of total CAC with acute coronary syndrome (ACS) and local CAC with culprit lesions in patients with suspected ACS. Methods: We performed computed tomography (CT) for CAC and CT angiography to assess the presence of significant stenosis and high-risk plaque (positive remodeling, low CT attenuation, napkin-ring sign, spotty calcium) in 37 patients with ACS and 223 controls. Total and segmental Agatston scores were measured. Culprit lesions were assessed in subjects with ACS. Results: Patients (n = 260) with vs. without ACS had higher total CAC score (median 229, 25 th -75 th percentile 75–517 vs. 27, 25 th -75 th percentile 0–99, p <0.001), higher prevalence of significant stenosis (78% vs. 7%, p <0.001) and high-risk plaque (95% vs. 59%, p <0.001). In those with ACS, culprit (n = 41) vs. non-culprit (n = 200) lesions, had similar segmental CAC score (median 22, 25 th -75 th percentile 4–71 vs. 14, 25 th -75 th percentile 0–51; p = 0.37 ), but higher prevalence of significant stenosis (81% vs. 11%, p <0.001) and high-risk plaque (76% vs. 51%, p =0.005). Significant stenosis (odds ratio 40.2, 95%CI 15.6–103.9, p <0.001) and high-risk plaque (odds ratio 3.4, 95%CI 1.3–9.1, p =0.02), but not segmental CAC score (odds ratio 1.0, 95%CI 1.0–1.0, p =0.47), were associated with culprit lesions of ACS. Conclusions: Total CAC burden was associated with ACS but segmental CAC was not associated with culprit lesions. Our findings suggest that total but not local CAC is a marker of ACS risk and support the hypothesis that extensive local CAC is a marker of plaque stability. Graphical abstract: Highlights: Total coronary artery calcium burden was a good predictor of acute coronary syndrome (ACS) in acute chest pain patients. Culprit lesions of ACS were characterized by significant stenosis and high-risk plaque. Culprit lesions of ACS had smaller amounts of coronary calcium. The prevalence of high-risk plaque was inversely related to segmental coronary calcium score. Local extensive coronary calcium may represent more stable stage of atherosclerosis.